Atmospheric limitations to astrometric detection of extra-solar planets with very large telescopes - Lazorenko, P. (Кинематика и физика небесных тел, 2005)
The report describes a new effective technique of atmospheric image motion suppression for observations with large ground-based one-aperture telescopes. The method is based on the use of an enhanced symmetrization of star reference fields. Another (optional) element of the technique is a special apodization of the telescope entrance pupil that is especially effective for extremely large (D > 30 m) apertures. Numerical simulations made for a 10 m telescope show that both atmospheric image motion and photon noise of the star images with a 10 min exposure can be reduced to less than 10 microarcsec. Evaluations refer to the Cn² vertical profile, which is typical for the Chilean astronomical sites, a moderate FWHM = 0.4" and star densities at galactic coordinates l = 0°, b = 20°. For a 100 m telescope, the precision is equal to 0.2 microarcsec/10 min for regions of high star density and drops to 1 microarcsec/10 min at the Galactic Pole. For the 10 m telescope, which measures astrometric reflex motion of stars with an accuracy of 10 microarcsec, a detection limit for Saturn- and Jupiter-sized planets is about 0.5–1 kpc. Application of very high precision astrometry is especially useful for searching extrasolar planets around the Pre-Main-Sequence, early Main-Sequence, and low-mass stars whose investigations with the aid of the radial velocity technique is difficult.